At the Roots of Neocolonialism: Forced Labor of the Indentured Chinese Miners in the British Transvaal - FITUNI Olga Leonidovna (Ученые записки Института Африки Российской академии наук)
The paper deals with the historical use of the Chinese indentured laborers on the gold mines of the Transvaal shortly after the end of the Second Boer war. In the short span of four years some 60 thousand Chinese laborers were imported under 3-year contracts, and then repatriated, after having contributed greatly to the restoration and expansion of the Rand gold mines. By analyzing the legal framework of the process and documented witnesses’ accounts of the “Chinese slavery” in the Transvaal, the author comes to the conclusion that the colonial administration of the Transvaal was ignoring the conventions agreed upon by the British and Chinese side, while the Chinese side did not possess the actual means to enforce the agreements. In the author’s opinion, this can be viewed as the roots of the West’s neocolonial approach to the international relations.